2018
DOI: 10.1124/jpet.117.247627
|View full text |Cite
|
Sign up to set email alerts
|

ONO-8590580, a Novel GABAAα5 Negative Allosteric Modulator Enhances Long-Term Potentiation and Improves Cognitive Deficits in Preclinical Models

Abstract: GABA receptors containing 5 subunits (GABA5) are highly expressed in the hippocampus and negatively involved in memory processing, as shown by the fact that GABA5-deficient mice show higher hippocampus-dependent performance than wild-type mice. Accordingly, small-molecule GABA5 negative allosteric modulators (NAMs) are known to enhance spatial learning and memory in rodents. Here we introduce a new, orally available GABA5 NAM that improves hippocampal functions. ONO-8590580 [1-(cyclopropylmethyl)-5-fluoro-4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The benzimidazole ONO-8590580 ( 40 , Figures and ) was recently described as an α5-GABA A R NAM . The affinity of this compound for the α5 subtype is 7.9 nM, which is around 3–30-fold higher than at α1-, α2-, or α3-GABA A Rs .…”
Section: α5-gabaar Namsmentioning
confidence: 99%
“…The benzimidazole ONO-8590580 ( 40 , Figures and ) was recently described as an α5-GABA A R NAM . The affinity of this compound for the α5 subtype is 7.9 nM, which is around 3–30-fold higher than at α1-, α2-, or α3-GABA A Rs .…”
Section: α5-gabaar Namsmentioning
confidence: 99%
“…Kawaharada et al reported that ONO-8590580 was a novel selective NAM of α5β3γ2 GABA A Rs. 69 ONO-8590580 concentration-dependently inhibited GABA-induced currents in HEK293 cells expressing α5β3γ2 GABA A Rs and also interacted with the benzodiazepine site within the receptors.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 96%
“…This ligand dramatically enhanced GABA-induced currents of α1β2γ2 GABA A Rs by binding to the benzodiazepine site at the α + –γ – subunit that is distant from orthosteric pockets in the ECD. Kawaharada et al reported that ONO-8590580 was a novel selective NAM of α5β3γ2 GABA A Rs . ONO-8590580 concentration-dependently inhibited GABA-induced currents in HEK293 cells expressing α5β3γ2 GABA A Rs and also interacted with the benzodiazepine site within the receptors.…”
Section: Allosteric Modulations Of Ligand-gated Ion Channels (Lgics)mentioning
confidence: 99%
“…Negative allosteric modulators targeted at specific receptor subtypes might also prove beneficial as shown in a recent study conducted at a5-containing receptors. 31…”
Section: From Gene To Functionmentioning
confidence: 99%